Pathophysiology : a 2-in-1 reference for nurses. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2004)
This unique 2-in-1 reference presents vital information on pathophysiology in two helpful ways on every page. The wide inner column contains detailed narrative text; the narrow outer column contains brief bulleted summaries of the same information. This format enables nurses to quickly scan the bulleted points and jump to in-depth information as needed without turning the page. Organized by body system, the book covers 220 diseases and disorders. Two 8-page full-color inserts illustrate selected disorders. Illustrations and flowcharts demonstrate abnormal structures and pathophysiologic proces.
Fundamentals of pathophysiology -- Cancer -- Infection -- Fluids and electrolytes -- Genetics -- Cardiovascular system -- Respiratory system -- Nervous system -- Gastrointestinal system -- Musculoskeletal system -- Hematologic system -- Immune system -- Endocrine system -- Renal system -- Integumentary system -- Reproductive system.
Includes bibliographical references and index.
Keywords: PHYSIOLOGY, PATHOLOGICAL